Early recognition of PIMS-TS: a single centre retrospective review - Mistry, Roshni (BMJ Paediatr Open, 2021)
INTRODUCTION: Research into paediatric inflammatory multisystem syndrome temporally associated with SARS-CoV-2 (PIMS-TS) has focused on tertiary level management. This review reports on symptoms and investigations at presentation. METHODS: Single centre retrospective case note analysis of patients fulfilling PIMS-TS diagnostic criteria from March to May 2020 in a London district level university hospital. RESULTS: Six patients presented in the week prior to their final diagnosis with fever and non-specific symptoms. Raised C-reactive protein (CRP), lymphopenia and hyponatraemia were noted. Kawasaki-like symptoms were under-represented in all patients. INTERPRETATION: The results suggest that a proportion of children with early PIMS-TS present with a non-specific febrile illness and abnormal blood results. Further research is needed to determine the most appropriate identification and follow-up of these children.